2016
DOI: 10.1121/1.4945097
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse ultrasound monitoring of stress and damage development on a 15-ton concrete beam

Abstract: This paper describes the use of an ultrasonic imaging technique (Locadiff) for the Non-Destructive Testing & Evaluation of a concrete structure. By combining coda wave interferometry and a sensitivity kernel for diffuse waves, Locadiff can monitor the elastic and structural properties of a heterogeneous material with a high sensitivity, and can map changes of these properties over time when a perturbation occurs in the bulk of the material. The applicability of the technique to life-size concrete structures is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 45 publications
3
80
0
3
Order By: Relevance
“…Their locations are in good agreement with observations made onsite at the outer surface (Fig. 1c), within a spatial uncertainty that corresponds to the Note that a data exclusion criterion was introduced based on the resolution index of the inverted model 16 . A resolution index reported by Vergely et al 22 is calculated to evaluate the quality of the inverted model: the more this index is close to one, the better the inverted model corresponds to the expected one 23 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Their locations are in good agreement with observations made onsite at the outer surface (Fig. 1c), within a spatial uncertainty that corresponds to the Note that a data exclusion criterion was introduced based on the resolution index of the inverted model 16 . A resolution index reported by Vergely et al 22 is calculated to evaluate the quality of the inverted model: the more this index is close to one, the better the inverted model corresponds to the expected one 23 .…”
Section: Resultssupporting
confidence: 83%
“…std m is determined using the L-curve method so as to determine the best trade-off between the regularization of the model and the data fitting 21 . For more technical considerations about the inversion approach, the reader is invited to refer to previous works 16 .…”
Section: Methodsmentioning
confidence: 99%
“…These sensitivity kernels can be used in inversion procedures, such as the LOCADIFF algorithm, for locating local changes to the material. [7][8][9][10][11] In concrete, one issue with CWI and ultrasonic methods in general is the high attenuation of highfrequency waves, caused by both scattering and intrinsic absorption. This attenuation, combined with often noisy environments for civil structures, means that the transducers cannot be separated by large distance before the signal-to-noise ratio (SNR) decreases below useful levels.…”
Section: Introductionmentioning
confidence: 99%
“…We find that the maximum value of scattering cross‐section σ reaches 4 m 2 /m 3 . This number has to be compared to previous works during mechanical experiments using intact concrete (Larose, Obermann, et al, ; Zhang et al, ) that found structural changes of the order of (0.1 ∼ 1 m 2 /m 3 ) for cracks developing in concrete. In the case of granite, there exists no specific experiment to compare to, so it is hard to discriminate which part of σ is due to reversible microdeformation and which part of σ is due to irreversible damage/microcracking developments.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a time‐lapse differential tomography technique named Locadiff (Larose et al, ) was developed to explore spatiotemporal changes based on analytical diffuse sensitive kernels together with a linearized inversion technique. Although Locadiff is still an ongoing project, the performance of this method was assessed through numerical studies (Pacheco & Snieder, ; Planès et al, ) and applied to imaging velocity changes and structural changes both in seismology (Obermann et al, , ) and in nondestructive testing and evaluation (Larose, Obermann, et al, ; Zhang et al, ). Using another inversion procedure, it even showed a potential to image high‐resolution subwavelength (∼1/15 λ , λ = 0.75 mm) changes (Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%